Quantifying the Trade-Off between Absolute Capacity and Rate Performance in Battery Electrodes - Coleman, Jonathan; Nicolosi, Valeria (My University, 2019)
Among other things, battery electrodes need to display large absolute capacities coupled with high rate performance. However, enhancing areal capacity, for example via increased electrode thickness, results in reductions in rate performance. The basis for this negative correlation has not been studied in a quantitative fashion. Here, a semiempirical model is used to analyze capacity versus rate data for electrodes fabricated from a number of materials, each measured at various thicknesses. Fitting the model to the data outputs the low‐rate areal capacity, QA, and the characteristic time associated with charge/discharge, τ, fit parameters which quantify absolute capacity and rate performance respectively. A clear correlation is found between QA and τ, with all data siting close to a mastercurve approximately defined by constant τ/QA. This data is consistent with a simple model based on the timescales associated with rate‐limiting processes. This model implies that the capacity‐rate trade‐off can be improved for high areal capacity electrodes by increasing the volumetric capacity, electrical conductivity, and porosity of the electrode. Conversely, solid‐state diffusion and reaction kinetics are only important for low areal capacity electrodes.
PUBLISHED
Keywords: Areal capacity; Energy density; Power density; Rate performance